2008
DOI: 10.1021/cm801539f
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Reduction of Vanadium Oxide Nanoscrolls: Crystal Structure, Morphology, and Electrical Properties

Abstract: The systematic and controlled reduction of vanadium oxide nanoscrolls results in routes to the largescale preparation of nanostructures of the interesting and useful materials rutile VO 2 and corundum V 2 O 3 . Vanadium oxide (V 2 O 5-δ ) nanoscrolls, prepared by the hydrothermal treatment of aged suspensions of V 2 O 5 and dodecylamine, were reduced in a furnace in an atmosphere of 5% H 2 :95% N 2 under different time and temperature conditions to monitor systematic trends in the structure and morphology of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 44 publications
1
70
0
3
Order By: Relevance
“…The limitations are not as stringent as they may seem, though, and it should be observed that metallic vanadium can be transformed to VO 2 by controlled oxidation [121][122][123][124] and that insulating V 2 O 5 van be transformed to VO 2 by controlled reduction in films. [125][126][127] There is a tendency that limited dimensions decreases c and widens the hysteresis in nanocrystalline films 46,48,[128][129][130][131][132][133][134][135] and nanorods. 27,28,81,90,118 This may be associated with internal stress in the particles.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations are not as stringent as they may seem, though, and it should be observed that metallic vanadium can be transformed to VO 2 by controlled oxidation [121][122][123][124] and that insulating V 2 O 5 van be transformed to VO 2 by controlled reduction in films. [125][126][127] There is a tendency that limited dimensions decreases c and widens the hysteresis in nanocrystalline films 46,48,[128][129][130][131][132][133][134][135] and nanorods. 27,28,81,90,118 This may be associated with internal stress in the particles.…”
Section: Discussionmentioning
confidence: 99%
“…3). 40,41 These porous structures are formed due to the loss of the amine intercalant, which acts as a sacrificial poreformer during the reduction process which is carried out at elevated temperatures. Fig.…”
Section: Reductionmentioning
confidence: 99%
“…Hollow nanospheres and microspheres of VO 2 , 6 15 and such coatings on carbon have been prepared chemically. 16 We also note that VO 2 nanoparticle infiltration into ordered polystyrene sphere arrangements have yielded inverse opal nanostructures, 17 that VO 2 "nanoscrolls" have been made from chemically prepared V 2 O 5Àd , 18 and that seaurchinlike nanostructures of VO x ÁyH 2 O have been deposited chemically 19 as well as electrochemically. 20 The mentioned research on VO 2 -based core-shell nanostructures represents examples of a huge endeavor to develop analogous structures of a vast range of materials, and representative recent work on hollow nanospheres-which will be shown below to have the most interesting properties for the case of VO 2 -has been presented for a multitude of other oxides including MgO, 21 SiO 2 , 22 c-MnO 2 , 23 NiO, 24 ZnO, 25 In 2 O 3 , 26,27 and SnO 2 .…”
Section: Introductionmentioning
confidence: 86%